Influence of essential oils and chitosan on quality attributes and shelf life of pineapple cv. Giant Kew at ambient storage - Mandal, Debashis; Takey, Bamin; Lalhruaitluangi , Noel (Journal of Postharvest Technology, 2022)
Pineapple is one of the important tropical fruits of Bromeliaceae family widely cultivated, consumed, and exported from India. Being a fruit of tropical origin and as mostly traded in ambient conditions within country caused high post-harvest loss and low shelf life. Essential oils as proven antimicrobial agent along with chitosan, as a protective barrier were targeted to use for the experiment. The present investigation was conducted to study the influence of chitosan and essential oils viz. lemon grass oil and basil oil, on quality attributes and shelf life of pineapple cv. Giant Kew at ambient storage (temperature of 20-25℃ and relative humidity 65-85%). Results of the study revealed that the coating of pineapple with chitosan (1%) along with lemon grass oil (0.5%) at 15 days after storage was the most effective in maintaining weight loss (8.84%), per cent decrease in fruit length (2.58%) and fruit diameter (3.97%) with highest fruit firmness (41.79 N). The same treatment also recorded highest TSS (15.25⁰Brix), TSS: Acid ratio (24.60), total sugar (7.41%), reducing sugar (6.13%) and ascorbic acid (24.54 mg 100g-1) content. Minimum fruit decay (6.67%) was observed in fruit treated with chitosan (1%) + lemon grass oil (0.5%) with maximum shelf life of 19.93 days.